In Vitro Functional Characterization of GET73 as Possible Negative Allosteric Modulator of Metabotropic Glutamate Receptor 5 - Beggiato, Sarah; Borelli, Andrea C.; Tomasini, Maria C.; Castelli, M. Paola; Pintori, Nicholas; Cacciaglia, Roberto; Loche, Antonella; Ferraro, Luca (Frontiers in Pharmacology, 2018)
The present study was aimed to further characterize the pharmacological profile of N-[4-(trifluoromethyl) benzyl]-4-methoxybutyramide (GET73), a putative negative allosteric modulator (NAM) of metabotropic glutamate subtype 5 receptor (mGluR5) under development as a novel medication for the treatment of alcohol dependence. This aim has been accomplished by means of a series of in vitro functional assays. These assays include the measure of several down-stream signalling [intracellular Ca++ levels, inositol phosphate (IP) formation and CREB phosphorylation (pCREB)] which are generally affected by mGluR5 ligands. In particular, GET73 (0.1 nM-10 µM) was explored for its ability to displace the concentration-response curve of some mGluR5 agonists/probes (glutamate, L-quisqualate, CHPG) in different native preparations. GET73 produced a rightward shift of concentration-response curves of glutamate- and CHPG-induced intracellular Ca++ levels in primary cultures of rat cortical astrocytes. The compound also induced a rightward shift of concentration response curve of glutamate- and L-quisqualate-induced increase in IP turnover in rat hippocampus slices, along with a reduction of CHPG (10 mM)-induced increase in IP formation. Moreover, GET73 produced a rightward shift of concentration-response curve of glutamate-, CHPG- and L-quisqualate-induced pCREB levels in rat cerebral cortex neurons. Although the engagement of other targets cannot be definitively ruled out, these data support the view that GET73 acts as an mGluR5 NAM and support the significance of further investigating the possible mechanism of action of the compound.